Exploring the perspective of Generation Z on personal risk management - Amelia Setiawan; Haryanto, Haryanto (SEAN Institute, 2024)
Every business aspires to be successful, and one critical pillar is incorporating effective risk management strategies. These strategies help minimize potential risks that may arise during the business's day-to-day operations. However, it is equally essential for individuals, particularly employees, to manage the risks in their daily activities. In light of this, this study extensively investigated the correlation between personality traits, privacy concerns, and personal risk management practices. Study design/methodology/approach: The study utilized Structural Equation Modeling Partial Least Squares (SEM PLS) to analyze the statistical data and draw more profound insights. Findings: The study found that an individual's approach to personal risk management is influenced by their personality traits, including agreeableness, conscientiousness, openness to experience, and privacy concerns. Interestingly, the only personality trait that positively and significantly impacted an individual's capability to manage financial risks was openness to experience. Research limitations/implications for practice: Regulators and academics should explore methods to increase public awareness of personal data protection. Recent research shows that Generation Z is only moderately concerned with privacy, indicating aneed for more awareness efforts. Campaigns, incorporating personal risk and privacy into education curricula, and publishing research findings can help raise awareness about these critical issues. However, education alone may not be sufficient to effect behavioral changes related to privacy risks. Originality/value of the results: The study's findings highlight the need for individuals to understand these factors, which are critical in effective personal risk management. Therefore, it is crucial to integrate personal risk management practices into organizations' overall risk management framework. This will equip individuals with the necessary skills to manage their risks effectively, leading to a safer and more secure working environment.